2011
DOI: 10.1183/09031936.00040211
|View full text |Cite
|
Sign up to set email alerts
|

Preschool asthma after bronchiolitis in infancy

Abstract: Asthma risk is lower after wheezing associated with respiratory syncytial virus (RSV) than with non-RSV infection in infancy. RSV is the main wheezing-associated virus in infants aged ,6 months. We evaluated the outcome of children hospitalised for bronchiolitis at ,6 months of age, with special focus on viral aetiology and early risk factors.Out of 205 infants hospitalised for bronchiolitis at ,6 months of age, 127 (62%) attended a control visit at a mean age of 6.5 yrs and the parents of an additional 39 chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
168
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(177 citation statements)
references
References 33 publications
5
168
2
2
Order By: Relevance
“…They found that RV-induced bronchiolitis (OR 3.3, 95% CI 1.0-11.1) and a positive family history for asthma (OR 2.5, 95% CI 1.2-4.9) were the strongest independent risk factors for recurrent wheezing and, therefore, concluded that a nasal washing positive for RV in infants hospitalised for bronchiolitis can possibly predict infants prone to the development of recurrent wheezing. These results concur well with a very recently published Finnish study in the European Respiratory Journal [19], in which children ,6 months of age hospitalised for bronchiolitis were followed at 6 yrs of age, demonstrating that the risk of asthma was lower after RSV bronchiolitis (8%) than after bronchiolitis caused by other viruses (24%). It will be interesting to see whether RVinduced bronchiolitis in the cohort of MIDULLA et al [18] remains a risk factor for the development of asthma at school age.…”
supporting
confidence: 82%
“…They found that RV-induced bronchiolitis (OR 3.3, 95% CI 1.0-11.1) and a positive family history for asthma (OR 2.5, 95% CI 1.2-4.9) were the strongest independent risk factors for recurrent wheezing and, therefore, concluded that a nasal washing positive for RV in infants hospitalised for bronchiolitis can possibly predict infants prone to the development of recurrent wheezing. These results concur well with a very recently published Finnish study in the European Respiratory Journal [19], in which children ,6 months of age hospitalised for bronchiolitis were followed at 6 yrs of age, demonstrating that the risk of asthma was lower after RSV bronchiolitis (8%) than after bronchiolitis caused by other viruses (24%). It will be interesting to see whether RVinduced bronchiolitis in the cohort of MIDULLA et al [18] remains a risk factor for the development of asthma at school age.…”
supporting
confidence: 82%
“…Doctor-diagnosed asthma was present at age 6.5 yrs in 12.7% of the 166 children hospitalised for bronchiolitis at age ,6 months. The figure was 8.2% in the former RSV patients versus 24% in the former non-RSV patients [3].…”
Section: Viral Wheezing Is Virus Specific and Not Just Host Specificmentioning
confidence: 95%
“…In long-term, prospective postbronchiolitis studies, 60% of the former bronchiolitis patients have wheezed at age 2-3 yrs and 15-40% have had doctordiagnosed asthma at school age [2]. However, if bronchiolitis has been caused by respiratory syncytial virus (RSV) [2], or has taken place at age ,6 months when RSV is the predominant causative agent [3], later asthma seems not to be substantially more common than in the non-selected population. Doctor-diagnosed asthma was present at age 6.5 yrs in 12.7% of the 166 children hospitalised for bronchiolitis at age ,6 months.…”
Section: Viral Wheezing Is Virus Specific and Not Just Host Specificmentioning
confidence: 99%
“…Data gathered so far demonstrate that both RSV and HRV represent an important risk factor associated with wheezing illness and subsequent increased risk of asthma development (Sigurs et al, 2010;Jackson et al, 2012) RSV is the major cause of LRT infections (LRTIs) in the first months of life. Epidemiological studies have clearly demonstrated that severe RSV bronchiolitis is frequently associated with subsequent persistent wheezing, childhood asthma or both (Stein et al, 1999;Gern and Busse, 2002;Henderson et al, 2005;Koponen et al, 2012). HRVs are the most commonly identified viruses involved in wheezing exacerbations in older infants and adolescents (Johnston et al, 1995;Busse and Gern, 1997;Rakes et al, 1999;Wennergren and Kristjansson, 2001;Heymann et al, 2004;Blanken et al, 2013).…”
Section: Introductionmentioning
confidence: 99%